Application of a novel approach of resistive‐type superconducting fault current limiter with a fast protection system in multi‐terminal direct current network. (17th August 2020) - Ayachi Amor, Yacine; Didier, Gaëtan; Hamoudi, Farid; Lubin, Thierry
Summary: The key obstacle in the realization of multiterminal high‐voltage direct current (MTDC) grids is the lack of existing commercial protection that a device can withstand the DC fault. Although different HVDC circuit breaker technologies have been investigated and demonstrators tested by manufacturers, the innovation of such devices to ensure a reliable protection system has not been proven yet due to the maximum breaking capability limitation especially in MTDC grids. To this, a combination of superconducting fault current limiter (SFCL) technology with a fast DC circuit breaker could bring a solution to this bottleneck. In this work, a new application of an accurate model of resistive‐type SFCL (rSFCL) considering both the electrical and thermal behaviors is proposed to work together with a proactive hybrid DC circuit breaker (PHCB) to fulfill the whole system protection. The viability of the proposed approach is verified under a worst DC fault case‐scenario that imposed in a five‐terminal MTDC meshed grid. The numerical analysis and simulations are carried out using (EMTP‐rv) software, while the obtained results show how significantly the proposed rSFCL can reduce the fault current and enhance the breaking capability. Also, a positive interaction has been observed between the rSFCL and PHCB in terms of design sizing and operation performance. Abstract : A new application of the second‐generation high‐temperature superconductor (2G HTS) of resistive‐type SFCL (rSFCL) is working together with a proactive hybrid DC circuit breaker to fulfill safe protection for a five‐terminal HVDC meshed grid that attending to be a part of European TWENTIES project.